Can a single coastal tide gauge help predict internal solitary wave activity offshore - Jean-Baptiste Roustan; Lucie Bordois; Jesús García-Lafuente; Franck Dumas; Francis Auclair; Xavier Carton (Scientific Reports)
Abstract Internal solitary waves (ISWs) propagate in stratified waters, enhancing diapycnal mixing, sediment and mass transport on shelves. They have typical wavelengths of hundreds of meters and tens of minutes periods, requiring high resolution and high frequency measurements for their sampling. But such in-situ measurements are scarce and ISWs remain largely unpredictable. We evidence that large amplitude ISWs propagating in the Strait of Gibraltar have a signature in the sea level at the Tarifa tide gauge and we propose an algorithm to automatically detect them. We validate the algorithm with in-situ measurements and satellite Sentinel-1 images. Thanks to the accuracy of this method, we analyse the ISW emission in the SoG from 2015 to 2023 from tidal to seasonal scales. This promising new method of in-situ ISW measurements offers potential benefits by supplying data on ISWs at various locations. These data will enhance our understanding of ISW dynamics, their parameterization and prediction.